Design Principles of Online Learning Communities in Citizen Science - Kermish-Allen, Ruth (Maine Policy Review, 2017)
Online communities for citizen science are expanding rapidly, giving participants the opportunity to take part in a wide range of activities, from monitoring invasive species to targeting pollution sources. These communities bring together the virtual and physical worlds in new ways that are egalitarian, collaborative, applied, localized and globalized to solve real environmental problems. Rural communities especially can leverage these learning and sharing spaces to take advantage of resources they would otherwise not be able to access. A small number of citizen science projects truly use an online community to connect, engage, and empower participants to make local change happen. This multiple case study looked at three online citizen communities that have successfully fostered online collaboration and on-the-ground environmental actions. The findings provide insight into potential design principles for online citizen science communities that support environmental actions in our backyards.
Keywords: citizen science; online platforms